Infectious diseases linked to the reproduction of canids and felids - Flores, Fabiano da Silva; Braga, Daiane Neis; Costa, Eliesse Pereira; Rosa, Carolina Cauduro da; Corrëa, Luis Felipe Dutra (Seven Editora, 2023)
The growing demand for companion animals such as dogs and breed cats has mobilized the trade, causing the number of kennels and cats to increase. In these establishments, there are some losses in the production of the reproduction of these animals. There is also a concern to keep some canids and wild felids that can sometimes be at risk of extinction or very close to it, with some in captivity enabling research of pathologies that can intervene in their procreation. Based on studies it is possible to verify that there are infectious diseases capable of harming in some way the reproduction of canids and felids, such as herpesvirus, toxoplasmosis, brucellosis, feline leukemia virus, and feline immunodeficiency virus. DOI:https://doi.org/10.56238/alookdevelopv1-021